Anterior, frontal congenital triangular alopecia, redundancy in therapy without improvement. Issue 6 (3rd October 2018) - Goldust, Mohamad; Rahmatpour Rokni, Ghasem; Sadr, Sara; Mirabi, Ali; Rezaee, Elham; Goren, Andy; Lotti, Torello
Abstract: Congenital triangular alopecia (CTA) is a benign noncicatricial localized pattern of hair loss with unknown etiology. Although referred to as "congenital, " CTA may develop in adulthood. It is believed that many cases of CTA are never diagnosed or are misdiagnosed; causing the incidence to be underestimated. The present study evaluates a case of 20‐year‐old woman presenting with a single circular to oval area of hair‐loss in the mid‐frontal region of her scalp. To date, about 170 cases of CTA have been reported and we present the first case in which the alopecic patch is located in the mid‐frontal region of the scalp. We present this case not only to challenge the preconceived notion that all CTAs are frontotemporal, but also to inform other practitioners about this rare condition and prevent redundant medical treatment.